Small molecule inhibitors of RAS-effector protein interactions derived using an intracellular antibody fragment - Camilo E. Quevedo (Nature Portfolio, 2018)
Intracellular antibodies can inhibit disease-relevant protein interactions, but inefficient cellular uptake limits their utility. Using a RAS-targeting intracellular antibody as a screening tool, the authors here identify small molecules that inhibit RAS-effector interactions and readily penetrate cells.